Comparative assessment of microstructure and texture in the Fe-30.5Mn-8.0Al-1.2C and Fe-30.5Mn-2.1Al-1.2C steels under cold rolling - Fabrício Mendes Souza (REM: International Engineering Journal)
Abstract Investigation of microstructure and texture has been done for cold rolled Fe-30.5Mn-8.0Al-1.2C (8Al) and Fe-30.5Mn-2.1Al-1.2C (2Al) (wt.%) steels. They were rolled to a strain of ~0.70. Refinement of a crystallographic slip band substructure in low to medium rolling strain and nucleation of twins on the mature slip bands at a higher strain were suggested as deformation mechanisms in the 8Al steel. Mainly shear banding contributed to the formation of a Copper texture in such steel. Brass-texture development in the 2Al steel is mainly due to deformation twinning and shear banding formation. Detailed images of KAM maps showed that the stored deformation energy was mainly localized in the twinned areas and shear bands, which generated the inhomogeneous deformation microstructures in both steels at a higher strain. Goss and Brass texture intensity decreases and Cu-texture intensity increases as the Al wt.% increases in different cold rolled High-Mn (Mn ~30 wt.%) steels.